AN ALGORITHM FOR COST ANALYSIS OF A UNIVERSITY FACULTY - Isherwood, Geoffrey B.; Rapagna, Socrates (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1978)
The climate of accountability that increasingly surrounds university financing led ta this study of the way in which funds were actually reaching students and programs within a particular university faculty. Concentrating on operating funds (mainly salaries) and on the numbers of students in courses, Isherwood and Rapagna were able to show differences in costs between departments, between graduate and undergraduate studies, and between degrees and diplomas of various "levels". The initial steps in achieving these results are the definition of the cost unit and the construction of the cast model; these are so defined as to be applicable not only to repetition of the cast analysis with the same faculty in the future, but also to other faculties engaged in quite different areas of teaching.